2008
DOI: 10.1007/s11064-008-9598-8
|View full text |Cite
|
Sign up to set email alerts
|

Dequalinium-Induced Cell Death of Yeast Expressing α-Synuclein-GFP Fusion Protein

Abstract: Intracellular toxic effects of the dequalinium-induced protofibrils of alpha-synuclein have been investigated with the yeast system expressing alpha-synuclein-GFP fusion protein in single copy, which appears in the green halo around the plasma membrane. Intracellular responses of the green fluorescent protein were analyzed as the cells were treated with dequalinium (DQ) and lactacystin. Yeast cells expressing alpha-synuclein-GFP were susceptible to both compounds in alpha-synuclein-dependent manner. Upon DQ tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Treatment of yeast cells expressing α-synuclein with the proteasome inhibitor lactacystin resulted in increased α-synuclein aggregation (Zabrocki et al, 2005; Lee et al, 2008). Consistently, expression of α-synuclein in the yeast strain sen3-1 , which harbors a mutation in the gene encoding the regulatory proteasome subunit Rpn2, led to increased steady-state levels of α-synuclein (using untagged α-synuclein) and to increased formation of aggregates (using GFP-tagged α-synuclein) (Sharma et al, 2006).…”
Section: Yeast Models Expressing Neurotoxic Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of yeast cells expressing α-synuclein with the proteasome inhibitor lactacystin resulted in increased α-synuclein aggregation (Zabrocki et al, 2005; Lee et al, 2008). Consistently, expression of α-synuclein in the yeast strain sen3-1 , which harbors a mutation in the gene encoding the regulatory proteasome subunit Rpn2, led to increased steady-state levels of α-synuclein (using untagged α-synuclein) and to increased formation of aggregates (using GFP-tagged α-synuclein) (Sharma et al, 2006).…”
Section: Yeast Models Expressing Neurotoxic Proteinsmentioning
confidence: 99%
“…Yeast cells overexpressing wild-type and disease-associated α-synuclein demonstrated growth deficits and age-dependent loss of clonogenic cell survival paralleled by the emergence of morphological markers of apoptosis and necrosis (Willingham et al, 2003; Flower et al, 2005; Witt and Flower, 2006; Büttner et al, 2008, 2013a,b; Lee et al, 2008; Su et al, 2010). The cellular accumulation of ROS and mitochondrial dysfunction are pivotal for the execution of α-synuclein-triggered cell death.…”
Section: Yeast Models Expressing Neurotoxic Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast cells overexpressing wild-type and disease-associated α-synuclein demonstrated growth deficits and age-dependent loss of clonogenic cell survival (Willingham et al, 2003; Flower et al, 2005; Witt and Flower, 2006; Büttner et al, 2008; Lee et al, 2008) (Table 1). α-Synuclein-triggered cytotoxicity in yeast was characterized by increased levels of ROS, and by the emergence of morphological markers of both apoptosis and necrosis (Flower et al, 2005; Büttner et al, 2008; Su et al, 2010).…”
Section: Neurotoxic Yeast Modelsmentioning
confidence: 99%
“…Mitochondria are critically damaged upon α-synuclein expression: (1) The mitochondrial network was fragmented (Sampaio-Marques et al, 2012), (2) mitochondria were found to be abnormally swollen (Su et al, 2010), (3) Cyt. c was released from mitochondria into the cytosol (Flower et al, 2005), (4) α-synuclein-expressing cells treated with the proteasome inhibitor lactacystin demonstrated loss of mitochondrial membrane potential (Lee et al, 2008), and (5) mRNA profiling revealed that 60% of the downregulated genes encode proteins localized to mitochondria (Yeger-Lotem et al, 2009). Mitochondrial damage pivotally contributes to α-synuclein-triggered cytotoxicity, because α-synuclein expression in ρ 0 cells, which lack mtDNA and are devoid of respiratory competent mitochondria, significantly relieved the loss of cell survival, reduced the number of apoptotic and necrotic cells and markedly decreased ROS levels (Büttner et al, 2008).…”
Section: Neurotoxic Yeast Modelsmentioning
confidence: 99%